Prenatal diagnosis for adenosine deaminase deficiency. Issue 2 (April 1981) - Ziegler, J B; Van der Weyden, M B; Lee, C H; Daniel, A
Abstract : Amniocentesis was performed in two successive pregnancies of the mother of a child with adenosine deaminase (ADA) deficient severe combined immunodeficiency. Assay of ADA in amniotic fluid fibroblasts showed the pregnancies to be normal and homozygous deficient, respectively. These findings were confirmed by the demonstration of a normal level of erythrocyte ADA in the cord blood of the healthy male born of the first pregnancy and by the demonstration of undetectable ADA activity in cord erythrocytes, spleen, liver, and kidney of the abortus of the second pregnancy. Prenatal diagnosis of ADA deficiency appears to be a reliable procedure.